Epidermolysis Bullosa Acquisita Occuring In A Patient With Systemic Lupus Erythematosus - setyowatie, Lita; Rahmawati, Yustian Devika; Widiatmoko, Arif; Retnani, Diah Prabawati (Universitas Muhammadiyah Malang, 2019)
Epidermolysis Bullosa Acquisita (EBA) is a rare, chronic autoimmune subepidermal bullous disease and has been noted to be associated with systemic lupus erythematosus (SLE). The incidence of EBA and SLE in one patient within the period of 1980-1990 found only 7 published case reports. A 23 years old woman with exfoliate skin since 12 years ago. Initially itchy on her buttock then appeared small blister. Blister spread almost the entire body and rupture. This complaint got worsening in a year accompanied with hair loss, weight loss, and oral ulcer. Dermatological examination showed patch eritematosa, hyperpigmentation, hypopigmentation, erotion with erythematous base, yellow brownish crust. Also obtained sclerodactyli toes and nail fingers. Laboratory examination anemia gravis, hypoalbuminemia, Coombs test +2, ANA Test negatif, dsDNA IgG 32,80. Histopathology examination showed blister subepidermal, no vacuolar degeneration, no superficial and deep infiltrat, and minimal lymphocyte. Patient had diagnosed SLE from Internal Department based on MEX-SLEDAI score. The patient was treated with metylprednisolone intravenous pulse dose 500 mg on 3 days then tappering off and wound care. Epidermolysis Bullosa Acquisita immunogenetically related with MHC class II haplotype in particular HLA-DR2. This factor suggest playing role in the development of EBA to express more aggresive SLE.